2023
DOI: 10.1002/jac5.1789
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pharmacist‐led discharge medication reconciliation at an Academic Medical Center

Abstract: Prior studies evaluating the impact of pharmacist‐led discharge medication reconciliation have demonstrated higher rates of medication discrepancy detection and intervention with variable effects on hospital readmission. The purpose of this study was to evaluate the impact of a newly developed pharmacist‐led hospital discharge medication reconciliation process implemented with an interdisciplinary Internal Medicine Service. This was a retrospective, single‐center, pre‐post observational cohort study. Instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…4,10,14 Similar to Muller et al, our internal medicine teaching services commonly serve an older patient populastandard PMRD process on patient safety. In our study, we utilized a simplified approach by applying an adapted NCC MERP Medication Error Index to describe potential harm and coupled that with physician consultation on the likelihood of an ED visit or hospital readmission.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…4,10,14 Similar to Muller et al, our internal medicine teaching services commonly serve an older patient populastandard PMRD process on patient safety. In our study, we utilized a simplified approach by applying an adapted NCC MERP Medication Error Index to describe potential harm and coupled that with physician consultation on the likelihood of an ED visit or hospital readmission.…”
mentioning
confidence: 89%
“…1,2 Pharmacist-led medication reconciliation at discharge (PMRD) has emerged as a potential solution to enhance medication safety by mitigating medication errors and reducing hospital readmissions. [3][4][5][6][7] Hospital discharge is a phase of care in which patients often become more vulnerable due to the absence of monitoring and assistance with medication administration. Previous publications from the Multi-Center Medication Reconciliation Quality Improvement Study have revealed a reduction in potentially harmful discrepancies in admission and discharge orders through a multifaceted medication reconciliation implementation model.…”
Section: Introductionmentioning
confidence: 99%